Peranan Kebebasan Akademik dalam Penyelamatan Sumber Daya Alam dan Antropologi Budaya - Basuki Wasis; Herlambang Perdana Wiratraman; Roedy Haryo Widjono (Sekolah Tinggi Kateketik Pastoral Katolik (STKPK) Bina Insan Keuskupan Agung Samarinda, 2021)
Saving natural resources, protecting the environment and preserving local culture is a tough job given the complexity of the problem. The way to uncover problems and environmental crimes and destroyers of natural resources is by